2017
DOI: 10.3389/fimmu.2017.00217
|View full text |Cite
|
Sign up to set email alerts
|

A Vaccine Therapy for Canine Visceral Leishmaniasis Promoted Significant Improvement of Clinical and Immune Status with Reduction in Parasite Burden

Abstract: Herein, we evaluated the treatment strategy employing a therapeutic heterologous vaccine composed of antigens of Leishmania braziliensis associated with MPL adjuvant (LBMPL vaccine) for visceral leishmaniasis (VL) in symptomatic dogs naturally infected by Leishmania infantum. Sixteen dogs received immunotherapy with MPL adjuvant (n = 6) or with a vaccine composed of antigens of L. braziliensis associated with MPL (LBMPL vaccine therapy, n = 10). Dogs were submitted to an immunotherapeutic scheme consisting of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 58 publications
3
30
0
2
Order By: Relevance
“…Currently, some markers related to protection have been studied, such as proinflammatory cytokines, production of immunoglobulins of IgG1 and IgG2 subtypes, and responsive CD4 + and CD8 + T-cells. The biomarkers that we chose are essential to determine resistance or susceptibility to visceral leishmaniasis and they are widely demonstrated in the literature [14,29]. Our data support that some peptides were able to induce lymphoproliferation and the production of IFN-γ by T-cells in vitro.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Currently, some markers related to protection have been studied, such as proinflammatory cytokines, production of immunoglobulins of IgG1 and IgG2 subtypes, and responsive CD4 + and CD8 + T-cells. The biomarkers that we chose are essential to determine resistance or susceptibility to visceral leishmaniasis and they are widely demonstrated in the literature [14,29]. Our data support that some peptides were able to induce lymphoproliferation and the production of IFN-γ by T-cells in vitro.…”
Section: Discussionsupporting
confidence: 67%
“…Dogs' Peripheral blood mononuclear cells (PBMCs) were isolated from heparinized blood by density centrifugation (Histopaque-1077 and 1119; Sigma-Aldrich, St. Louis, MO, USA). The PBMCs (5 × 10 5 cells/well) were CFDA-SE (Carboxyfluorescein diacetate succinimidyl ester)-labeled according to the Roatt, et al [14] protocol and cultured in triplicate in a 48-well flat-bottom plate (Costar, Cambridge, MA, USA). The cells were stimulated or not with the synthetic peptide (1 µg/mL), SLA (100 µg/mL), and concavalin A (3 µg/mL) mitogen for 120 h at 37 • C and 5% CO 2 .…”
Section: In Vitro Peptide Screening-lymphoproliferation and Intracellmentioning
confidence: 99%
“…Notably, the vaccine composed of L. braziliensis antigens associated with MPL adjuvant (LBMPL vaccine) in symptomatic dogs was able to trigger increased CD3 + T lymphocytes and their subpopulations, a reduction in CD21 + B lymphocytes, and an increase in NK cells and CD14 + monocytes. Moreover, the dogs exhibited an important decline in the number and intensity of disease symptoms, increased body weight, reduced splenomegaly, and a drop in the parasite burden (Roatt et al, 2017). Similarly, Viana et al (2018) demonstrated that L. amazonensis antigens, alone or in association with saponin (LaSap therapeutic vaccine), used in symptomatic dogs improved their clinical status, reduced IgG serum levels, and triggered a lymphoproliferative profile using L. infantum antigens, resulting in an outstanding reduction in parasite load.…”
Section: Immunotherapy and Immunochemotherapy As Strategies For Impromentioning
confidence: 93%
“…Although, CVL treatment cannot induce parasite clearance, this measure has been largely employed, thus demonstrating the dogs' close relationship in our society. In this sense, immunotherapeutic treatments have shown to be promising against CVL, with the main objective of reestablishing dog immunity and, therefore, parasite control (Roatt et al, 2017). This approach can be performed alone or in combination with chemotherapy (Singh and Sundar, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Após esse tratamento, os cães apresentaram uma melhoria significativa nos sinais clínicos, diminuição da IL10 e aumento na produção de IL2 e IFNγ, com redução no parasitismo cutâneo, demonstrando a eficácia da imunoterapia em doença sintomática LV. 35,43 Promovendo indução de proteção contra a leishmaniose, uma vacina ideal contra a LCan deve ter características imunológicas que incluem a elicitação de uma resposta imune mediada por células duradouras e a capacidade de provocar uma resposta em toda a população vacinada. Vários estudos relataram o potencial de diferentes vacinas candidatas a desencadearem mecanismos imunoprotetores contra a LCan.…”
Section: Introductionunclassified